Role of Ag microalloying on glass forming ability and crystallization kinetics of ZrCoAgAlNi amorphous alloy. (January 2021) - Surendar, A; Geetha, K; Rajan, C; Alaazim, M
Abstract : Bulk metallic glasses (BMGs) with new chemical compositions (ZrCoAgAlNi) were fabricated and the effects of Ag minor addition on the glass forming ability (GFA) and crystallization kinetics were studied. The x-ray diffraction (XRD) test was applied to identify the amorphousness of BMGs or possible crystalline phases. Using differential scanning calorimeter (DSC), the thermal stability and crystallization kinetics under a non-isothermal condition at the different heating rates were studied. Considering the heating rate dependency of glass transition and crystallization kinetics, the activation energy was evaluated and measured for the mentioned processes. It was revealed that the rise in Ag content led to the decrease in activation energy for glass transition, while the activation energy for crystallization increased. The thermal stability and GFA were also studied and it was found that the Ag addition strongly affected the inherent features of BMGs. With the increase in Ag content, the atomic mobility and structural rearrangement changed in the material and consequently, the GFA and thermal stability were significantly improved.